The Identification of the Information Quanta in Semantic Network: A basis for the Structural Analysis in Ontology Evaluation - Amirhosseini, Maziar (International journal of information science and management, 2023)
The following article proposes a novel context by Information Quanta in the structural analysis of ontologies, which could be used to develop ontology evaluation metrics and measures. The identification of information quantum needs to clarify knowledge quanta in knowledge systems and semantic networks by considering two influential theories as Quantum Theory of Knowledge (QTK) proposed by Burgin (1995a; 1997; 2004) and the Semantic Link Theory of Knowledge (SLTK) proposed by Zhuge (2004; 2010; 2012). QTK identifies the quantum level of knowledge as knowledge quanta comprising the minimal blocks or units of knowledge in the construction of knowledge systems. In this case, knowledge quanta are primitive propositions and predicates. Elementary units of semantic networks, the triad of two nodes and a labeled semantic link between them, in SLTK based on the Semantic Link Network Theory (SLNT) could be conceptualized as knowledge quanta. Quantum units of knowledge are shared representations in the QTK and the SLTK. As a kind of semantic network, ontology also includes the triads of nodes and semantic links defined as knowledge quanta here. A semantic link as a knowledge quantum can be divided into its components, i.e., into three parts: subject, object, and relation. These separate parts can be considered as the information quantum or semantic network data. Finally, it can be said that the information quantum or data in the semantic network of ontologies that include the subject, object, and relation are derived from the fragmentation of the semantic links into their components. Identifying information quanta in ontologies could play an influential role in establishing and developing a new context in the structural analysis of ontologies through proposing, developing and applying new metrics and criteria in measurement of the mentioned quantum elements (i.e., ontology data).